CONCEPTUAL CHANGE THEORY AS A TEACHING STRATEGY IN ENVIRONMENTAL EDUCATION - Agiande, Denis U.; James J. Williams; Albert Y. Dunnamah; Danbiyu P. Tumba (European Scientific Journal, ESJ, 2015)
The theory of conceptual change came to education as an analogy drawn from the history and philosophy of science as a result of the difficulties people experienced in changing from one explanatory framework to another. Today, other fields of enquiries like environmental education are charged with the task of helping learners in formal and non-formal educational settings to change their long held conceptions, ideas and attitudes which are domineering, destructive and unsustainable towards the environment to a healthier, sustainable and preserving ones that provides the necessary knowledge and skills to solve existing problems and prevent further ones from threatening our harmonious existence with nature. This paper examines the Conceptual Change Model (CCM) proposed by (Posner, Strike, Hewson & Gertzog, 1982) as a variant of the conceptual change theory and how this theory can be applied in environmental education (E.E.) teaching and learning. In an attempt to change misconceptions, practices and attitudes among learners in formal education. The paper practically examines the tenets of the theory and show how it can be used to discover learners’ misconceptions about some aspects of the environment and how it can be applied along with other teaching/learning tools in environmental education to affect permanent change in behaviours.